2015
DOI: 10.1002/hbm.22906
|View full text |Cite
|
Sign up to set email alerts
|

Neuroticism and conscientiousness respectively constrain and facilitate short‐term plasticity within the working memory neural network

Abstract: Individual differences in cognitive efficiency, particularly in relation to working memory (WM), have been associated both with personality dimensions that reflect enduring regularities in brain configuration, and with short‐term neural plasticity, that reflects task‐related changes in brain connectivity. To elucidate the relationship of these two divergent mechanisms, we tested the hypothesis that personality dimensions, which reflect enduring aspects of brain configuration, inform about the neurobiological f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 36 publications
4
32
0
1
Order By: Relevance
“…Meanwhile, our results suggested that individuals with well‐organized, persistence and self‐discipline tend to process information more efficiently and economically, which showed good agreement with previous reports. For example, the relationship between the L p in dlPFC and neuroticism/conscientiousness was also highlighted in previous studies, in which they discovered that neuroticism and conscientiousness, respectively, constrained and facilitated neuroplastic responses within the working memory networks, which includes the dlPFC, parietal, and anterior cingulate cortex (Dima, Friston, Stephan, & Frangou, 2015). Interestingly, previous studies also demonstrated that compromised small‐world properties in dlPFC was associated with reduced levels of effort control, which was related with psychopathology in young children (Fekete et al., 2014).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Meanwhile, our results suggested that individuals with well‐organized, persistence and self‐discipline tend to process information more efficiently and economically, which showed good agreement with previous reports. For example, the relationship between the L p in dlPFC and neuroticism/conscientiousness was also highlighted in previous studies, in which they discovered that neuroticism and conscientiousness, respectively, constrained and facilitated neuroplastic responses within the working memory networks, which includes the dlPFC, parietal, and anterior cingulate cortex (Dima, Friston, Stephan, & Frangou, 2015). Interestingly, previous studies also demonstrated that compromised small‐world properties in dlPFC was associated with reduced levels of effort control, which was related with psychopathology in young children (Fekete et al., 2014).…”
Section: Discussionmentioning
confidence: 67%
“…Several limitations of this study should be mentioned here. First, although the validity and reliability of NEO‐FFI is stable, we cannot fully exclude subjective judgment because it is a self‐report measurement (Dima et al., 2015). Second, only the dlPFC is involved in this study, which somehow ignores the influence from other brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we predicted that conscientiousness was linked to variations in cortical anatomy in PFC and parietal regions that belong to the multiple demand system (DeYoung, 2010; Kapogiannis et al , 2012; Duncan, 2013; Forbes et al , 2014; Dima et al , 2015; Rodrigo et al , 2016). …”
Section: Introductionmentioning
confidence: 99%
“…The collective and cumulative impact of low Conscientiousness may thus be to amplify or accelerate ε4 memory deficits. Disrupted connectivity in working memory tasks has also been recently reported among younger individuals low in Conscientiousness(Dima et al, ), as have greater cortical atrophy (Jackson et al, ) and neurofibrillary tangles(Terracciano et al, ) in older persons. By contrast, ε4 carriers in this sample who exhibited more Conscientiousness evidenced memory performance comparable to ε2 carriers or ε3 homozygotes.…”
Section: Discussionmentioning
confidence: 81%